1995
DOI: 10.1002/ange.19951071711
|View full text |Cite
|
Sign up to set email alerts
|

Dialkylammonium‐Ionen/Kronenether‐Komplexe: Vorläufer einer neuen Familie „mechanisch”︁ verknüpfter Moleküle

Abstract: 90.67(2)", V = 1675 A3, 2 = 2, p,,.,. = 1.54 p(CuKJ = 21.4 em-', 4216 unabhangige Reflexe, 2411 davon beobachtetmit IF,I > 4u(~FJ). 28 <110",Verfeinerung zu R = 0.138, R, = 0.157. Siemens-P4/PC-Diffraktometer fur 3 ' 2PF6 und 4 4PF6 und Siemens-P4/

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(35 citation statements)
references
References 20 publications
1
34
0
Order By: Relevance
“…[35] Compound II was prepared as described elsewhere. [22] Gold nanocrystals, stabilized by chemisorbed I, were prepared following the method reported by Brust et al: [36] HAuCl 4 (0.155 g) in deionized H 2 O (15 mL) was added to a phase transfer catalyst nOct 4 NBr (1.101 g) in CDCl 3 (12 mL), and the resulting mixture stirred vigorously for approximately 10 min. The organic layer was recovered, the stabilizer (I, 0.070 g) in CDCl 3 (4 mL) and the reducing agent (NaBH 4 , 0.190 g) in H 2 O (13 mL) added, and the resulting mixture stirred overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…[35] Compound II was prepared as described elsewhere. [22] Gold nanocrystals, stabilized by chemisorbed I, were prepared following the method reported by Brust et al: [36] HAuCl 4 (0.155 g) in deionized H 2 O (15 mL) was added to a phase transfer catalyst nOct 4 NBr (1.101 g) in CDCl 3 (12 mL), and the resulting mixture stirred vigorously for approximately 10 min. The organic layer was recovered, the stabilizer (I, 0.070 g) in CDCl 3 (4 mL) and the reducing agent (NaBH 4 , 0.190 g) in H 2 O (13 mL) added, and the resulting mixture stirred overnight at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The search for novel protocols that can be utilized for the supramolecular synthesis [3] of new classes of pseudorotaxanes, by self-assembly, [4] has led us to develop [5] supramolecular systems that are based upon the mutual recognition between secondary dialkylammonium ions and macrocyclic polyethers of varying constitutions. We have demonstrated that the composition of the pseudorotaxane superarchitecture is dependent on the size of the macroring employed for the supramolecular synthesis (Figure 1): by way of illustration, only one NH 2 -containing strand can be passed through the cavity of the dibenzo [24]crown-8 (DB24C8) macroring, [5a, 5c±e, 5g] whereas two such strands can be fed through its larger congener bis-p-phenylene [34]crown-10 (BPP34C10), [5b±e] which acts, in this instance, as a ditopic coreceptor.…”
Section: Introductionmentioning
confidence: 99%
“…Of these self-assembling systems, secondary dialkylammonium ions (R 2 NH 2 + ) are well-known for their ability to thread through, for example, a dibenzo [24]crown-8 (DB24C8) ring to give a [2]pseudorotaxane, [5] owing to a combination of strong [ + N À H···O] hydrogen bonding and [CÀH···O] interactions. Upon deprotonation of the R 2 NH 2 + moiety, the two [ + NÀH···O] hydrogen bonds are eliminated, and the [2]pseudorotaxanes are dethreaded.…”
mentioning
confidence: 99%